ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) Dan KADMIUM (Cd) PADA UDANG WINDU (Penaeus monodon) DI PERAIRAN BENIUNG TARAKAN KALIMANTAN TIMUR DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Rais Razak; Siti Masyitah (Fakultas Farmasi UMI, 2013)
The research have done to analysis of metal weigth lead (Pb) and Cadmium (Cd) at Windu Prawn (Penaeus monodon) in Beniung territorial water Tarakan East Kalimantan by Atomic Absorbtion Spectrophotometry (SSA). The research enwrap qualitative and quantitative analysis. Before to be analised, first to do destruction of Windu Prawn (Penaeus monodon) later on disolved in HNO3 and HCl. Qualitative analysis used reactant specific and quantitative analysis used atomic absorbtion spectrophotometry (SSA) at wave length of 217,0 nm and 228,8 nm for lead and cadmium respectively. Result of research find average rates of Pb metal and cadmium letal in Beniung territorial water Tarakan East Kalimantan is 0,7636 ppm and is 0,4730 ppm. From result of research to showing that average rates Pb and Cd metal to Beniung territorial water Tarakan East Kalimantan, it is not over from sill limit and according to DIRJEN POM regulation.Key Words : Analysis, Pb, Cd, Penaeus monodon, Atomic Absorbtion Spectrophotometry